Systematic Review: Impact of Air, Leachate, and Soil Contamination on Health Problems in Landfill Workers and Local Residents - Nabilah Zahra; Mursid Raharjo; Sulistiyani Sulistiyani; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: The rising global production of municipal solid waste (MSW) poses significant ecological challenges. In developing countries, inadequate landfill management results in the uncontrolled release of hazardous gases and leachate, posing significant risks to human health. This systematic review investigated the association between environmental factors at these landfills and adverse human health outcomes. Methods: This review was conducted in accordance with the PRISMA guidelines. A comprehensive search was rapidly conducted across ScienceDirect, Scopus, PubMed, and EBSCOhost for articles published between 2020 and 2025. PECO criteria screening was conducted independently by two reviewers, resulting in the selection of 25 articles for critical synthesis. Results: Hazardous landfill pollutants—including heavy metals, volatile organic compounds (VOCs), and particulate matter—are rapidly escalating severe health issues. Residents and landfill workers face acute respiratory and cardiovascular disorders, heightened cancer risk, reproductive issues, and neurological impairments. Leachate contamination of soil and groundwater compounds these urgent systemic risks. Conclusion:The ongoing failure to manage landfills effectively, particularly in developing countries, has triggered a pressing environmental and public health crisis. Immediate action to improve waste management and enforce stricter environmental policies is critical for preventing further harm.